Critical periods during childhood and adolescence: a study of adult height among immigrant siblings - Gerard J. van den Berg; Petter Lundborg; Paul Nystedt; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2009)
We identify the ages that constitute critical periods in children's development towards their adult health status. For this we use data on families migrating into Sweden from countries that are mostly poorer, with less healthy conditions. Long-run health is proxied by adult height. The relation between siblings' ages at migration and their heights after age 18 allows us to estimate the causal effect of conditions at a certain age on adult height. Moreover, we compare siblings born outside and within Sweden. We apply fixed-effect methods to a sample of about 9,000 brothers. We effectively exploit that for siblings the migration occurs simultaneously in calendar time but at different developmental stages (ages). We find important critical periods at ages 5/6 and 9. The effects are stronger in families migrating from poorer countries but weaker if the mother is well-educated.
urn:nbn:de:101:1-20090513381
Keywords: I10; I12; I18; F22; I20; I30; J10; N30; 330; Early-life conditions; migration; parental education; adult health; height retardation; age; fetal programming; developmental origins; Kinder; Gesundheit; Persönlichkeitspsychologie; Lebensverlauf; Migranten; Schweden